Determination of ash values of some medicinal plants of genus sesbania of marathwada region in maharashtra - Momin, R K; B, Kadam V (Journal of Phytology, 2011)
The seasonal variation of total ash, water soluble ash and water insoluble ash have been investigated leaves , wood and bark of Sesbania grandiflora, Sesbania bispinosa and Sesbania cannabina, which are medicinally important. Comparative account of total ash, water soluble ash and water insoluble ash content of bark of Sesbania grandiflora showed high level of total ash (rangeÂ 11.80 to 12.10 %) and low level of total ash of leaves of Sesbania cannabina ( range 5.05 to 5.35 % ) .The water soluble ashÂ showed higher level of wood of Sesbania grandiflora (range 4.30 to 4.80 % ) and lower in leaves of Sesbania cannabina (range 1.5 to 2.05 %),Comparative account of water insoluble ash of bark of Sesbania grandiflora showed higher (range 7.20 to 7.35 % ) and lower in the leaves of Sesbania bispinosa (range 2.9 to 3.1 % ). <!–EndFragment–> Â